Effect of High Intensity Interval Training on Selected Physical Fitness and Performance Variables Among College Men Sprinters - E., Chellappa; Louis Raj, Y.C. (Journal of Neonatal Surgery, 2025)
This study sought to determine how high-intensity interval training affected specific physical fitness and performance metrics in male collegiate sprinters. To execute the present study the research investigator, select 15 college men sprinters from KMG College of Arts and science and Govt Thirumagal mills College of Arts and science Gudiyattam Vellore Dist. The training group namely interval training group underwent their training program for 8 weeks. Alternative days the work out lasted for 45 to 60 minutes including warm-up and warm-down exercises. The subjects underwent their training program apart from their regular routine. The selected Physical fitness variables namely speed and Agility, and performance variables namely 100m and 200m are dependent variables. Independent variable was High Intensity Interval Training. To determine the significant difference between pre and post test the statistical procedure namely paired “t” test was applied. To test the level of significance the 0.05 level was fixed. The results of the information analysis showed that the use of High Intensity Interval Training greatly enhanced the chosen dependent variable, namely Speed Agility 100m and 200m.